2021
DOI: 10.1029/2020ja028589
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Ionospheric Day‐To‐Day Variability Over Wuhan Based on Ionosonde Measurements and Model Simulations

Abstract: Day-today variability is ubiquitous in the ionosphere. Investigating and understanding the behavior is an important subject for the space environment. Previous studies proposed that ionospheric variability is mainly driven by three sources, including variations in solar activity and geomagnetic activity from above and lower atmospheric perturbations from below. Some general features of ionospheric day-today variability have been observed. Forbes et al. (2000) concluded that the variability in F2 peak electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The difference is supposed to be affected by the solar activity. Although, to our knowledge, no clear evidence has been reported that the level of solar activity could influence the tidal day‐to‐day variabilities in the MLT region, the low solar activity is indeed in favor of the tidal propagation into the thermosphere (Oberheide et al., 2009, 2011b) and generating the ionospheric day‐to‐day variability (Liu, 2020; Zhou et al., 2020, 2021) due to the lower dissipation under solar minimum condition. Whether the solar activity control the MLT tidal day‐to‐day variabilities or not and the corresponding mechanism are worthy of more detailed simulated investigation to provide exact evidence in the future.…”
Section: Discussionmentioning
confidence: 95%
“…The difference is supposed to be affected by the solar activity. Although, to our knowledge, no clear evidence has been reported that the level of solar activity could influence the tidal day‐to‐day variabilities in the MLT region, the low solar activity is indeed in favor of the tidal propagation into the thermosphere (Oberheide et al., 2009, 2011b) and generating the ionospheric day‐to‐day variability (Liu, 2020; Zhou et al., 2020, 2021) due to the lower dissipation under solar minimum condition. Whether the solar activity control the MLT tidal day‐to‐day variabilities or not and the corresponding mechanism are worthy of more detailed simulated investigation to provide exact evidence in the future.…”
Section: Discussionmentioning
confidence: 95%
“…The strong difference below 100 km may be attributed variations due to processes in the lower atmosphere which are not taken into account. For example, features of day‐to‐day variability during solar minimum conditions or during nighttime are not well represented by TIE‐GCM, which is likely due to missing variations of perturbations from the lower atmosphere (Zhou et al., 2021). The quality of the ionosonde data must also be considered for the discussion of the observed differences, because uncertainties in the N e profiles are to be expected despite the consideration of only data with AQI of 2 and 3.…”
Section: Simulation Of the Height‐dependent Delayed Ionospheric Responsementioning
confidence: 99%
“…Strong agreement between the observed climatology of the IT region and the modeled climatology [from models like the Thermosphere-Ionosphere-Electrodynamics General Circulation Model (TIEGCM), its predecessor the Thermosphere General Circulation Model (TGCM), and the Whole Atmosphere Community Climate Model with thermosphere and ionosphere eXtension (WACCM-X)] has been demonstrated since as early as 1981 (Dickinson et al, 1981;Richmond et al, 1992;Fesen et al, 2002;Qian et al, 2014;Liu et al, 2018), but the day-to-day variations are comparatively difficult to model/study and therefore less understood (Zhou et al, 2020, Zhou et al, 2021Andoh et al, 2022). Many details of the state of the IT system can be captured by parameters such as the ratio of atomic Oxygen (O) to molecular Nitrogen (N 2 ) (O/N 2 ).…”
Section: Introductionmentioning
confidence: 99%